Angiotensin II causes cellular proliferation in infantile haemangioma via angiotensin II receptor 2 activation. Issue 5 (23rd February 2015) - Itinteang, Tinte; Marsh, Reginald; Davis, Paul Frank; Tan, Swee Thong
Abstract : Aims: To investigate the effect of the angiotensin peptides and their agonists and antagonists on cellular proliferation in proliferating infantile haemangioma (IH) in vitro explants. Methods: Proliferating IH samples from six patients were cultured in vitro in the presence of angiotensin I (ATI) alone, or AT1 and the ACE inhibitor, ramipril, or ATII alone, or ATII with the ATII receptor 1 (ATIIR1) blocker, losartan, or ATII with the ATIIR2 blocker, PD123319, or the ATIIR2 agonist, CGP42112. After 6 days in culture, the IH tissue pieces were harvested, formalin-fixed and paraffin-embedded. The effect of each treatment type on cellular proliferation was evaluated by immunohistochemical staining of these tissue pieces using the proliferation marker, Ki67. Results: There was a significant increase in cellular proliferation in the ATI and ATII treated IH tissues compared with control samples. Their effect on cellular proliferation was reduced by adding ramipril and PD123319, respectively. CGP42112, but not losartan, significantly increased cellular proliferation. Conclusions: Our findings suggest a key regulatory role of ATI and ATII in promoting cellular proliferation in IH, and establish a role for ACE and ATIIR2 in the proliferation of this tumour.